1990
DOI: 10.1111/j.1524-4725.1990.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed‐Dye Laser Treatment of Leg Telangiectasia: With and Without Simultaneous Sclerotherapy

Abstract: Thirty consecutive female patients with red leg telangiectasia less than 0.2 mm in diameter were treated with a Candela SPTL-1 Pulsed Dye Laser (PDL) tuned to 585 nm with a pulse duration of 450 microseconds at energies ranging from 6.0 to 8.5 J/cm2 delivered through a 5-mm spot size to the entire length of the telangiectasia. Seven patients with 25 patches of telangiectatic matting after previous sclerotherapy were also treated. Twenty-seven patients with symmetrical telangiectatic patches or a large "starbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 48 publications
2
42
0
1
Order By: Relevance
“…However, attempts at using the PDL to treat leg telangiectasia have until now been notably unsuccessful except for the smallest vessels, those measuring 0.2 mm in diameter or smaller [1]. For example, Polla et al [2] treated 35 leg telangiectasias with the Candela PDL using a 577 nm wavelength, 0.36-msec pulse duration, and 1-, 2-, and 3-mm-diameter spot sizes.…”
Section: Introductionmentioning
confidence: 98%
“…However, attempts at using the PDL to treat leg telangiectasia have until now been notably unsuccessful except for the smallest vessels, those measuring 0.2 mm in diameter or smaller [1]. For example, Polla et al [2] treated 35 leg telangiectasias with the Candela PDL using a 577 nm wavelength, 0.36-msec pulse duration, and 1-, 2-, and 3-mm-diameter spot sizes.…”
Section: Introductionmentioning
confidence: 98%
“…Dierickx et al 11 studied an 800-nm diode laser with a water-cooled sapphire tip (Star Medical Tech Inc, Pleasanton, Calif) for the treatment of leg telangiectasia. Telangiectasia less than 0.4 mm in diameter were treated with a 20-millisecond duration pulse at a fluence of 40 J/cm 2 . Approximately 25% of telangiectasia cleared after 1 treatment, 50% after 2 treatments, and 75% after 3 treatments, with vessels greater than 0.4 mm in diameter demonstrating better clearance than smaller ones.…”
Section: -13mentioning
confidence: 99%
“…[1][2][3] Although sclerotherapy remains the gold standard of treatment, its drawbacks include the discomfort and phobia of injections, postsclerotherapy hyperpigmentation, telangiectatic matting, and allergy to the sclerosing agent. 4,5 In addition, the success of the treatment depends on the technical skill and experience of the physician performing sclerotherapy.…”
mentioning
confidence: 99%
“…In our study, this group showed the best results, even though the KTP (532) laser method for treatment of spider leg veins cannot be considered ideal with a success rate of 33%. Sclerotherapy of spider leg veins with similar diameters is at least as important as laser therapy [26]. In 40%, a reduction in diameter compared to the initial situation was achieved and in 27%, no change occurred.…”
Section: Discussionmentioning
confidence: 99%